Masjid Wadi Al-Hussein of Narathiwat, Southern Thailand: the unforgotten Islamic architectural heritage - Salleh, Nurul Hamiruddin; Abdul Hadi, Adli Hadi (Nova Science Publishers, 2025)
The present study examines the architectural evolution and cultural significance of Masjid Wadi Al-Hussein, also known as Masjid Teluk Manok, located in Lubosawo, Narathiwat, Southern Thailand. Established in the 1600s, this masjid (mosque) is one of the oldest Islamic structures in the region and serves as a key example of vernacular Malay architecture blended with Javanese influences and Islamic symbolism. Over nearly 400 years, Masjid Wadi Al-Hussein has undergone multiple phases of development, each reflecting changes in the socio-political and religious landscape of the local Malay Muslim community. This study focuses on the masjid’s structural systems, materials, ornamentation, and spatial organisation, documenting how the building’s design has evolved to meet the needs of its congregation while preserving its historical and religious significance. Using a combination of architectural analysis, field measurements and historical documentation, it explores the influences of local climate, materials, and Islamic religious practices on the masjid’s design. Particular attention was given to the use of traditional construction techniques, such as timber post-and-beam systems, the application of Singgora clay tiles for passive cooling, and the symbolic meaning of carvings and calligraphy. The present study also highlights the challenges of heritage conservation in tropical climates, where humidity and environmental factors threaten the longevity of timber structures. It concludes by emphasising the importance of preserving such heritage buildings, not only for their architectural value but also for their role in maintaining the cultural and religious identity of the local community. This study contributes to the broader discourse on Islamic architecture and heritage conservation in Southeast Asia, offering insights into sustainable preservation practices for future generations.